HUBUNGAN KEPERCAYAAN DIRI DENGAN TINGKAT KECEMASAN PADA MAHASISWA KELAS ALIH TRANSFER PROGRAM SARJANA KEPERAWATAN - Syafrullah, Haidir; rokayah, cucu; Nurdini, Resti (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2017)
Kepercayaan diri adalah suatu sikap, perasaan yakin atas kemampuan diri sendiri. Mahasiswa dengan kepercayaan diri positif memiliki kemampuan untuk mencapai tujuan dalam hidup, tidak akan mudah menyerah dan mudah mengalami kecemasan dalam menghadapi kesulitan pada saat menyusun skripsi. Penelitian bertujuan untuk mengetahui hubungan antara kepercayaan diri dengan tingkat kecemasan.Metode penelitian bersifat deskriptif korelasi dengan pendekatan cross-sectional. Populasi penelitian sebanyak 70 sampel dengan  metodetotal sampling. Instrumen penelitian berupa kuisioner kepercayaan diri Lauster  dan kuesioner DASS (Depression Anxiety Stress Scale). Hasil penelitian menunjukkan tingkat kepercayaan diri positif 35 orang (50%) dan tingkat kecemasan berat 9 orang (12,86%) serta terdapat hubungan yang signifikan antara kepercayaan diri dengan tingkat kecemasan (p-value = 0,009), mahasiswa kelas alih tranfer tingkat akhir program studi sarjana keperawatan di STIKes Dharma Husada Bandung. Saran untuk  institusi pendidikan melalui pembimbing akademik dapat memberikan lebih banyak motivasi dan sugesti positif terhadap mahasiswa yang tengah menyusun skripsi dan diadakan bimbingan dan konseling kepada mahasiswa. Kata Kunci: Kepercayaan Diri, Tingkat Kecemasan THE RELATIONSHIP BETWEEN SELF-CONFIDENCE AND ANXIETY LEVEL ON THE STUDENT OF LAST GRADE BACHELOR PROGRAMME IN NURSING WHO WERE IN THE TRANSFERRED-CLASS AT DHARMA HUSADA BANDUNG  INSTITUTE OF HEALTH SCIENCE ABSTRACTSelf-confidence is a certain attitude or feeling of self-assurance. Students with positive self-confidence have the ability to achieve goals in their life. They would not give up nor easily experience anxiety, when facing difficulties at the time of preparing their thesis. The study aimed to determine the relationship between self-confidence and the level of anxiety. The research method was descriptive correlation with cross-sectional approach. The research population was 70 samples and total sampling method was used. The research instruments were Lauster self-confidence questionnaire  and anxiety level questionnaire with DASS (Depression Anxiety Stress Scale) measurement scale. The results showed that 35 people (35%) positive self-confidence leveland 12.86% with very heavy anxiety level and  significant correlation between self-confidence and the level of anxiety (p-value = 0.009)  on the students of Dharma Husada Bandung Institute of Health Science who were in the transferred-class at their final semester. The research suggested the educational institutions, through the supervisors, to provide more positive motivations and suggestions for the students who were in their thesis preparation and to held counseling for the students with very heavy anxiety level. Keywords: Anxiety Level,  Self Confidence